Situation at the University of Priština 1975–1981 Based on Writings from the Newspaper "Novi svet" - Miketić, Uroš D. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
The Novi svet, the Serbian-language student newspaper of the University of Priština, provides valuable testimony about the local situation between 1975 and 1981. Although the newspaper does not reflect disturbed interethnic relations at the university, it is highly critical of university policy in several respects. This particularly refers to the half-hearted implementation of university reform, whose proclaimed goal was broad modernization and the advancement of personnel educated at the institution. At the same time, the newspaper offered praise for areas where genuine efforts were made to strengthen this young higher education institution, especially in terms of student standards and extracurricular activities. Overall, the university’s development was constrained by the socio-economic and political circumstances in Kosovo, and its considerable potential remained underutilized.